Use of human albumin infusion in cirrhotic patients: a systematic review and meta-analysis of randomized controlled trials - Bai, Zhaohui; Wang, Le; Wang, Ran; Zou, Meijuan; Méndez-Sánchez, Nahum; Romeiro, Fernando Gomes [UNESP]; Cheng, Gang; Qi, Xingshun (Springer Nature, 2022)
Background: Human albumin infusion is effective for controlling systemic inflammation, thereby probably managing some liver cirrhosis-related complications, such as spontaneous bacterial peritonitis (SBP), hepatic encephalopathy (HE), and hepatorenal syndrome. However, its clinical benefits remain controversial. Methods: EMBASE, PubMed, and Cochrane Library databases were searched. Randomized controlled trials (RCTs) regarding use of human albumin infusion in cirrhotic patients were eligible. Mortality and incidence of liver cirrhosis-related complications were pooled. Effect of human albumin infusion on mortality was also evaluated by subgroup analyses primarily according to target population and duration of human albumin infusion treatment. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. Results: Forty-two RCTs were finally included. Meta-analysis showed that human albumin infusion could significantly decrease the mortality of cirrhotic patients (OR = 0.81, 95% CI = 0.67–0.98, p = 0.03). Subgroup analyses showed that human albumin infusion could significantly decrease the mortality of cirrhotic patients with SBP (OR = 0.36, 95% CI = 0.20–0.64, p = 0.0005) and HE (OR = 0.43, 95% CI = 0.22–0.85, p = 0.02), but not those with ascites or non-SBP infections or undergoing large-volume paracentesis. Short-term human albumin infusion treatment could significantly decrease short-term mortality (OR = 0.67, 95% CI = 0.50–0.89, p = 0.005), but not long-term mortality. Long-term human albumin infusion treatment could not significantly decrease long-term mortality (OR = 0.72, 95% CI = 0.48–1.08, p = 0.11). In addition, human albumin infusion could significantly decrease the incidence of renal impairment (OR = 0.63, 95% CI = 0.45–0.88, p = 0.007) and ascites (OR = 0.45, 95% CI = 0.25–0.81, p = 0.007), but not infections or gastrointestinal bleeding. Conclusions: Human albumin infusion may improve the outcomes of cirrhotic patients. However, its indications for different complications and infusion strategy in liver cirrhosis should be further explored.
Keywords: Ascites; Gastrointestinal bleeding; Hepatic encephalopathy; Human albumin; Infection; Liver cirrhosis; Meta-analysis; Mortality; Renal impairment; Spontaneous bacterial peritonitis